Analysis of the Stromal Cellular Components of the Solid Tumor Microenvironment Using Flow Cytometry - Timaner, Michael; Beyar-Katz, Ofrat; Shaked, Yuval (Current protocols in cell biology, 2016)
The tumor microenvironment consists of a variety of cell types. The contribution of each cell type to the tumor is an emerging subject in the field of cancer research. Here, we describe protocols for dissociating tumor tissues and Matrigel plugs into single cells for further analysis by flow cytometry. These protocols can be used for evaluating the cellular component of solid tumors from human or mouse origin or Matrigel plugs implanted in mice. The protocols describe the dissociation of tumor tissue with or without dissociation automatic devices. Subsequently, the use of flow cytometry for immunophenotypic analysis of host cells found in the tumor microenvironment, including myeloid derived suppressor cells, endothelial cells, and macrophages is provided. These methods can be used to broaden our understanding of the cross-talk between tumor and host cells in the tumor microenvironment. © 2016 by John Wiley & Sons, Inc.